Drug incompatibility in the ICU: review of implications in nursing practice - Graciele Oroski Paes; Samara Oliveira Moreira; Maiara Benevides Moreira; Tamiris Gonçalves Martins (Universidade Federal de Goias, 2017)
This is an integrative review of the literature performed in seven databases, with the aim of analyzing the scientific production on potential drug incompatibilities in ICUs, and mapping the most prevalent incompatible drugs described in the literature. The filters applied were: articles available in full, and publications from 2009 to 2016 in Portuguese, English, and/or Spanish, totaling 11 articles at the end of the selection. From the review, it was observed that the medicines phenytoin and pantoprazole are the main drugs responsible for drug incompatibilities in intensive care units. Blocking of incompatibilities can be achieved through simple measures routinely implemented by the nursing team, such as optimization of drug scheduling, administration of drugs known to be incompatible in separate venous routes, and standardization of drug dilution and administration, focusing mainly on the most prevalent incompatible drugs found in the study.